2020
DOI: 10.1093/ageing/afaa067
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medication use in older adults with mild-moderate Alzheimer’s disease: prevalence and associations with adverse events

Abstract: Abstract Aim Potentially inappropriate medication (PIM) use is prevalent in older adults and is associated with adverse events, hospitalisation and mortality. We assessed the patterns and associations of PIM use in older adults with mild-to-moderate Alzheimer’s Disease (AD), who may represent a particularly vulnerable group. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…For aged patients with cancer, the PIM rate ranged from 47.3% to 73% 33,34 . Murphy 35 found that 55.8% older adults with mild-to-moderate Alzheimer disease were prescribed a PIM with 30.1% being prescribed 2 and more PIMs in nine European countries. For older adults with diabetes, from 56% to 66.2% cases had at least 1 PIM 36, 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For aged patients with cancer, the PIM rate ranged from 47.3% to 73% 33,34 . Murphy 35 found that 55.8% older adults with mild-to-moderate Alzheimer disease were prescribed a PIM with 30.1% being prescribed 2 and more PIMs in nine European countries. For older adults with diabetes, from 56% to 66.2% cases had at least 1 PIM 36, 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Murphy 35 found that benzodiazepines, SSRIs and Proton Pump Inhibitors (PPIs) were the most frequent PIMs. Roux 31 found that benzodiazepines, PPIs, antipsychotics, antidepressants were the most prevalent PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…According to systematic analyses of global disease burden in 2017, dementia is the fifth leading cause of death in China ( Zhou et al, 2019 ). Potentially inappropriate medication (PIM) may be one of the reasons leading to death in older people with dementia, and extensive studies have also shown that the occurrence of PIM leads to an increased risk of adverse events and hospitalizations, even death ( Cross et al, 2017 ; Wallace et al, 2017 ; Murphy et al, 2020 ). Thus, it is necessary to determine PIM use and risk factors among older patients with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…All types of medication-related harm (MRH) have been recognized by the WHO as a global public health issue [4,5]. The importance of MRH is rising and has become one of the main causes of hospital admission [6][7][8], even after a recent discharge [9,10]. Special strategies and criteria for avoiding MRH were developed and regularly updated to mitigate druginduced problems, polypharmacy, and age-related alterations in drug handling [11,12,13].…”
Section: Introductionmentioning
confidence: 99%